2017
DOI: 10.1136/ejhpharm-2017-001368
|View full text |Cite
|
Sign up to set email alerts
|

Audit of a multidisciplinary approach to improve management of community-acquired pneumonia

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is a frequent cause of morbidity, mortality and hospital admission worldwide. An adequate choice of empirical antibiotic treatment and appropriate severity assessment of the disease are key aspects in the management of CAP.ObjectiveTo audit the adherence to standards of care, such as empirical prescribing of antibiotics, and evaluate the current multidisciplinary approach to the management of CAP.MethodRecords of patients with CAP were identified and examined for CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The decision to admit and the antimicrobial choice for CAP have been highly protocolised based on well-validated scoring systems, including CURB-65 for patients presenting to hospital [4] , [5] . Despite this, documentation of severity scores for unscheduled admissions has been poor [6] , [7] , [8] , [9] , [10] . Patients with low CURB-65 scores are admitted unnecessarily [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The decision to admit and the antimicrobial choice for CAP have been highly protocolised based on well-validated scoring systems, including CURB-65 for patients presenting to hospital [4] , [5] . Despite this, documentation of severity scores for unscheduled admissions has been poor [6] , [7] , [8] , [9] , [10] . Patients with low CURB-65 scores are admitted unnecessarily [11] .…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced by a study conducted in Italy by Costantini et al in 2012, adherence to both urinary antigen tests was reported at 55% for all patients [29]. Conversely, a study in the United Kingdom by Fahimi et al demonstrated a markedly lower compliance rate, with less than 20% of physicians adhering to the testing protocol [32]. In Ireland, both pre-and post-intervention results exhibited compliance rates below 20% and up to 40%, respectively [33].…”
Section: Urine Legionella and Pneumococcal Antigen Testingmentioning
confidence: 97%
“…This finding aligns closely with the results of other audits conducted in similar healthcare settings. For instance, at James Paget University Hospital in the United Kingdom, blood cultures were obtained for 84.2% of cases [32]. Likewise, at Sligo University Hospital in Ireland, the pre-interventional and post-interventional rates for blood culture collection were 84.4% and 62.5%, respectively [33].…”
Section: -Obtaining Two Pairs Of Blood Cultures In Hospitalized Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Рекомендовано участие врачей-специалистов в диагностике и ведении детей с пневмонией в зависимости от тяжести течения заболевания и коморбидной патологии с целью эффективной терапии [70] (УУР -С; УДД -5). Диагностику и ведение пациентов с пневмонией обычно проводит врач-педиатр / врач общей практики (семейный врач), при необходимости проводятся консультации врача-пульмонолога, врача детского хирурга / врача торакального хирурга.…”
Section: иные диагностические исследованияunclassified